Photoelectric Effect on Metal Work Function Using Test Simulation - Kazman Riyadi; Ahmad Salleang; Nisty Taqhira (Indonesian Journal of Advanced Research, 2023)
Some physical materials are microscopic, atomistic or abstract in nature which are difficult to observe directly. Although observations can be made experimentally, the high cost of laboratories and materials in experiments is an obstacle to conducting tests in experiments. This can hamper the teaching and learning process, especially in basic physics courses. The development of computerization has touched the learning environment. Computer simulations have been able to visualize the actual state of the scientific phenomenon. This can be a solution to the problem. The purpose of this paper is to compare the test results using PhET (Physics Education Technology) simulations with theoretical calculations on the photoelectric effect on the work function of metals. The results obtained by the wavelength simulation (λ) for the work function of Sodium 547 nm, Zenc 430.8 nm, Copper 264 nm and 195 nm with the highest and lowest difference between theory and simulation tests on sodium material are 1.39% while for Zenc it was 0.03%.